Design Scheme of Bidirectional Converter Device in Urban Rail Transit Traction Power Supply System and Comprehensive Benefits - KANG Chonghao; ZHOU Wenwei; HU Jianqiang (Chengshi guidao jiaotong yanjiu)
［Objective］ At present, the bidirectional converter device in the traction power supply system of urban rail transit (hereinafter referred to as "urban rail") in China is in the promotion stage, and there exist multiple configuration schemes with practical applications. It is necessary to comprehensively evaluate the pros and cons of each scheme, unify the technical standards, and simultaneously conduct a benefit analysis of the device whole life cycle，so as to provide a basis for decision-making in engineering applications. ［Method］ Based on the advantages of the bidirectional converter device in terms of equipment function, DC traction power supply capability, comprehensive energy saving, and power quality, etc., and considering factors such as floor area, equipment investment, power quality, economic benefits, and reliability, a technical and economic comparison and selection of the existing five configuration schemes for the bidirectional converter device in China are carried out, and a recommended configuration scheme is proposed. In the case study of a certain urban rail main line, the comprehensive benefits of the bidirectional converter device in the whole life cycle in terms of energy saving, reactive power compensation, and stray current protection are analyzed. ［Result & Conclusion］ Through comprehensive comparison and selection, the scheme of one set of diode rectifier unit plus one set of bidirectional converter unit is recommended for the bidirectional converter device, which has the lowest cost in its whole life cycle. Adopting this scheme, it is estimated that the 20-year total life cycle cost of the above-mentioned urban rail main line will be reduced by 2.568 million yuan/km.